Karateristik Perusahaan, Tipe Auditor dan Konsentrasi Kepemilikan Saham terhadap Pengungkapan Modal Intelektual - Jacobus Widiatmoko; Maria Goreti Kentris Indarti (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2018)
This study aimed to examine the effect of the characteristics of companies consisting of two variabels are profitability and leverage, the type of auditor, and the concentration of ownership on the disclosure of intellectual capital. In this study, the firm size is used as a control variable. The population in this study are manufacturing companies listed in Indonesia Stock Exchange (IDX) in 2012-2014. Samples were selected by using purposive sampling method and the results obtained 86, 92, 92 companies respectively for each year. By using regression analysis technique of ordinary least square (OLS), the results are profitability and leverage positive effect on the intellectual capital disclosure. Meanwhile, the auditor type and concentration of ownership has no effect on the intellectual capital disclosure.Firm size as control variable showed result in line with its function, which is a significant positive effect.